Chromosomal disorders in Triticum aestivum subject to prolonged radionuclide pollution of soil from the Exclusion Zone of the Chornobyl Nuclear Power Plant - YakymchukR. А.; Morgun, V. V.; ChyzhevskyiІ. V. (Regulatory Mechanisms in Biosystems, 2024)
Due to the large number of nuclear power plants around the globe and the growing threat of radioactive accidents, a complex assessment of the biological consequences of the Chornobyl disaster is a relevant issue. Study of mutagenic activity of prolonged and chronic action of radionuclide pollution of soil in the Chornobyl Exclusion Zone long after the accident will allow us to identify the current level of threat they pose to the human genome and can reveal specific cytogenic markers of radionuclide environmental pollution. For this purpose, we germinated seeds of wheat of soft winter varieties Smuhlianka and Bohdana in soil samples from the Chornobyl Exclusion Zone 35 years after the disaster. Specific activity of Cs-137 and Sr-90 accounted for 4.5–28.2 kBq/kg. To determine the frequency and range of chromosomal aberrations, we used the anaphase-telophase method. In aberrant cells, we studied extracellular distribution of chromosomal disorders. The frequency of aberrant cells was 3.53–7.55 times above the spontaneous level. High mutagenic activity remained in the conditions of the lowest density of radionuclide pollution of soil. The range of chromosomal disorders mostly included paired fragments and bridges and containd chromosomal acentric rings, binding of chromosomes, myocardium, and lagging and leading chromosomes. Radionuclide pollution in the Chornobyl Exclusion Zone induced multiple cellular aberrations in the rhizome meristem, the share of which was the highest in case of low specific radionuclide pollution of soil, and exhibited a tendency towards decrease against the background of the highest density of radionuclides. Pollution of the environment with radionuclides as a result of disasters at nuclear energy objects poses a threat to the human genome and is a global problem, requiring state support to solve through systematic genetic monitoring in readionuclide-polluted territories and areas adjacent to them.